(untitled) (Physical Culture and Sport: Scientific Perspective, 2025)
The article presents the results of the assessment of the effectiveness of a typical program for building a training process for rowers-academics of higher qualification (men’s national team of Ukraine) in the preparatory period of the annual macrocycle for the stage of maximum realization of individual capabilities. To achieve the goal of the study, the features of changes in the indicators of general and special physical fitness of athletes specializing in academic rowing at the beginning and end of the training period were studied using traditional methods, a computer program for express assessment of general physical fitness "ShVSM" and a rowing simulator "Concept-2". In order to most objectively assess the results of the study, we also developed model characteristics of the general physical fitness of athletes of higher qualification specializing in academic rowing. The results of the study allowed us to state the overall positive impact of the typical program of organizing the training process on the main indicators of the current level of general and special physical fitness: by the end of the preparatory period, a significant increase in the aerobic capabilities of the examined athletes, general and speed endurance, thigh muscle strength, average rowing pace at a distance of 2000 m and 6000 m was observed. At the same time, changes in other indicators of general and special physical fitness had only a tendency to improve. In addition, by the end of the preparatory period, the surveyed academic rowers recorded significant deviations in the indicators of general physical fitness from the model characteristics: at the beginning of the preparatory period, the values ​​of these deviations were 14% for the relative values ​​of maximum oxygen consumption, 20% for the relative values ​​of РВС170 and the level of speed endurance, 29%-32% for the levels of speed-power and general endurance, 25% for the level of general physical fitness, and by the end of this period, the decrease in these values ​​was insignificant (from 3 to 5%). Thus, the results of the study indicate the insufficient effectiveness of the typical program for building a training process for academic rowers of higher qualification in the preparatory period of the annual macrocycle and the need for its significant improvement, taking into account the main requirements of the modern level of development of academic rowing in the world and the latest achievements of IT technologies.